Appropriation of Digital Competence in Teacher Education - Elen Instefjord (Universitetsforlaget, 2015)
The aim of the article is to explore opportunities for appropriation of digital competence in teacher education. Digital competence is knowledge, skills and attitudes required in order to use technology critically and reflectively in the process of building new knowledge. According to Wertsch learning to use a cultural artefact is characterized by two processes: mastery and appropriation. The article reports from a case study of two teacher education institutions. Findings indicate that the same challenges are found in both institutions: the conflict between mastery and appropriation, and between personal and educational use of technology, and the resistance towards technology among some teacher educators. The results signify that in order to create opportunities for appropriation of digital competence and encourage use of technology as part of pre-service teachers' professional didactic competence, technology should be better integrated as pedagogical tools for teaching and learning in all subjects in the teacher education programmes.